3D Carbon/Cobalt‐Nickel Mixed‐Oxide Hybrid Nanostructured Arrays for Asymmetric Supercapacitors. Issue 14 (18th March 2014) - Zhu, Jianhui; Jiang, Jian; Sun, Zhipeng; Luo, Jingshan; Fan, Zhanxi; Huang, Xintang; Zhang, Hua; Yu, Ting
<x xml:space="preserve">Abstract</x> The electrochemical performance of supercapacitors relies not only on the exploitation of high‐capacity active materials, but also on the rational design of superior electrode architectures. Herein, a novel supercapacitor electrode comprising 3D hierarchical mixed‐oxide nanostructured arrays (NAs) of C/CoNi3O4 is reported. The network‐like C/CoNi3O4 NAs exhibit a relatively high specific surface area; it is fabricated from ultra‐robust Co‐Ni hydroxide carbonate precursors through glucose‐coating and calcination processes. Thanks to their interconnected three‐dimensionally arrayed architecture and mesoporous nature, the C/CoNi3O4 NA electrode exhibits a large specific capacitance of 1299 F/g and a superior rate performance, demonstrating 78% capacity retention even when the discharge current jumps by 100 times. An optimized asymmetric supercapacitor with the C/CoNi3O4 NAs as the positive electrode is fabricated. This asymmetric supercapacitor can reversibly cycle at a high potential of 1.8 V, showing excellent cycling durability and also enabling a remarkable power density of ∼13 kW/kg with a high energy density of ∼19.2 W·h/kg. Two such supercapacitors linked in series can simultaneously power four distinct light‐emitting diode indicators; they can also drive the motor of remote‐controlled model planes. This work not only presents the potential of C/CoNi3O4 NAs in thin‐film supercapacitor applications, but it also demonstrates the superiority of electrodes with such a 3D hierarchical architecture.